King Kong vs. Godzilla - Honda, Inoshiro; Koizumi, Hajime; Takashima, Tadao; Fujiki, Yû; Sahara, Kenji (Criterion, 2019)
After his first two cinematic rampages, Godzilla was revived as an adversary for the Hollywood import King Kong. When Kong is discovered on a remote island by a publicity-hungry pharmaceutical company, the giant ape is set on a collision course with Godzilla, and Japan braces for a double dose of devastation. Both the Japanese-release version and the U.S.-release cut were rousing hits, cementing Godzilla’s status as a series-worthy star. [www.criterion.com]
Keywords: Blu-Ray-Disc